Penerapan Media Ajar Berbasis Audio Visual Pada Pelajaran IPAS di SDN 2 Kutadalom - Akbar Rahman; Teo Randra Arifin; Sela Syapira Oktari; Sadza Navisa Yusra; Ahmad Daffa Rizaldo; Dinan Kurniawan; Ike Ferawati (Jurnal Kabar Masyarakat, 2024)
The development of technology and information has an impact on education, so media is very important in the learning process. The use of learning media for educators as a tool to deliver material in the teaching and learning process. Through learning media, students will more easily receive the knowledge delivered. One of the learning media is audio visual which can be applied in Natural and Social Sciences (IPAS) lessons. This study aims to analyze the effectiveness of the application of audio visual-based teaching media in Natural and Social Sciences (IPAS) subjects at SDN 2 Kuta Dalom. By utilizing audio visual technology, it is hoped that students can better understand the subject matter in a more interesting and interactive way. This study uses a quantitative method with an experimental approach. The results of the study showed a significant increase in student understanding after the application of audio visual-based teaching media.